2021
DOI: 10.1002/lno.11788
|View full text |Cite
|
Sign up to set email alerts
|

Pico‐ and nanoplankton communities on a near to offshore transect along the continental shelf of the northwestern Gulf of Mexico in the aftermath of Hurricane Harvey

Abstract: Hurricane Harvey delivered over 124 trillion liters of freshwater to the Texas-Louisiana coast and the northwestern Gulf of Mexico (GOM) in late August-early September 2017. Environmental conditions, size-fractionated phytoplankton biomass, and pico-and nanoplankton abundances (picocyanobacteria, picoeukaryotes, autotrophic, and heterotrophic nanoplankton) were characterized along nearshore-offshore transects prior to Hurricane Harvey (late July 2017) and in the 3 weeks to 6 months following the storm (Septemb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 61 publications
2
12
0
Order By: Relevance
“…Conversely, high salinities indirectly reduced zooplankton evenness via greater water column stratification. Lower fluorescence at higher salinities supports the spatial patterns in NWGOM phytoplankton identified by Kurtay et al 20 following Hurricane Harvey. Those authors observed declines in overall phytoplankton abundance and communities increasingly dominated by cells < 20 µm in size waters along a coastal to oceanic gradient.…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…Conversely, high salinities indirectly reduced zooplankton evenness via greater water column stratification. Lower fluorescence at higher salinities supports the spatial patterns in NWGOM phytoplankton identified by Kurtay et al 20 following Hurricane Harvey. Those authors observed declines in overall phytoplankton abundance and communities increasingly dominated by cells < 20 µm in size waters along a coastal to oceanic gradient.…”
Section: Discussionsupporting
confidence: 83%
“…The PSEM “multigroup” analysis showed that relationships between salinity and primary production (i.e., fluorescence) switched signs and was reduced by an order of magnitude after Harvey. This reflects the post-Harvey shift in underlying phytoplankton community, towards smaller heterotrophic organisms reported by Kurtay et al 20 . Finally, we see that after Harvey, higher temperatures led to lower zooplankton community evenness whereas the reverse was true for non-storm years.…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations